Combustion and agglomeration of aluminized high-energy compositions; IOP Conference Series: Materials Science and Engineering; Vol. 93: Modern Technique and Technologies (MTT'2015) - Korotkikh A. G. Aleksandr Gennadievich; Arkhipov V. A.; Glotov O. G.; Slusarskiy (Slyusarsky) K. V. Konstantin Vitalievich (Materials and technologies new generations, 2015)
Title screen